A Primer on Real Effective Exchange Rates: Determinants, Overvaluation, Trade Flows and Competitive Devaluation - Chinn, Menzie D. (My University, 2005)
The author discusses alternative measures of effective exchange rates in the context of their theoretical underpinnings and actual construction. Focusing on contemporary indices and recently developed econometric methods, he examines the empirical characteristics of these differing series, including the exchange rates for the United States, the euro area and several East Asian countries. Case studies illustrate the issues that confront the applied economist or policymaker in using the measures of real effective exchange rates available.